Loss & damage from climate change: from concept to remedy?. (2nd July 2020) - Doelle, Meinhard; Seck, Sara
ABSTRACT: In this article we examine legal perspectives on remedies for harm caused by climate related loss and damage. We start by discussing the meaning of loss and damage, and its relationship to climate mitigation and adaptation. We then consider, at a conceptual level, how those harmed by loss and damage from human-induced climate change may pursue remedies against those who have contributed to the harm suffered. Key policy insights Loss and damage is an issue that requires the attention of law and policy makers at domestic and international levels While existing legal systems are unlikely to be adequately equipped in their present form to respond adequately to claims for remedy to harm caused by loss and damage, they will be challenged to evolve over time to respond more effectively Legal systems will be challenged to identify appropriate claimants, appropriate respondents, appropriate remedies and actionable wrongs Different legal systems will make different choices on these critical issues.